Reflections on the Physical or Visceral Mode of Argumentation in Michael Gilbert’s Theory of Multi-Modal Argumentation and its Relation to Gesture Studies and The Embodied Mind - Duran, Claudio (Informal Logic, 2022)
In this paper I question the primacy of argumentation relying solely on logic by showing how the body and mind are deeply connected and as a result how communication and argumentation are a product of this mind/body connection. In particular, I explore the physicality of argumentation through the research and writings on gestures and the embodied mind. Michael Gilbert’s theory of multi-modal argumentation provides the general approach for this elaboration.